Applying Nightingale charts to evaluate the heterogeneity of biomedical waste in a Hospital - Janini Cristina Paiz; Marcio Bigolin; Vania Elisabete Schneider; Nilva Lúcia Rech Stedile (Universidade de São Paulo, 2014)
OBJECTIVES: to evaluate the heterogeneity of biomedical waste (BW) using Nightingale charts.METHOD: cross-sectional study consisting of data collection on wastes (direct observation of receptacles, physical characterisation, and gravimetric composition), development of a Management Information System, and creation of statistical charts.RESULTS: the wastes with the greatest degree of heterogeneity are, in order, recyclable, infectious, and organic wastes; chemical waste had the most efficient segregation; Nightingale charts are useful for quick visualisation and systematisation of information on heterogeneity.CONCLUSION: the development of a management information system and the use of Nightingale charts allows for the identification and correction of errors in waste segregation, which increase health risks and contamination by infectious and chemical wastes and reduce the sale and profit from recyclables.